(3GSGSjGJ GdGSJKeGQ aj HhQUI GdGhQGb GdeGdjI (B/s - (3Mfaj, YHO GdZaGQs ((3GdGScfOQjI(B: s (3OGQ GdLGeYjI(B, s, 2001)
(3GdGSJKeGQ hGShGb GdGhQGb GdeGdjI(B- (3GdGSJKeGQ aj GdGhQGb GdeGdjI, GShGb GdGhQGb GdeGdjI, eDTQGJ GdGSge bjGS YGFO heNGWQGdGhQGb GdeGdjI(B-(3JMdjd hJbhje GdGSge(B-(3JMdjd hJbhje GdSfOGJ(B-(3GShGb QCS GdeGd aj eUQ(B-(3GdNjGQGJs
(3HjHdjhZQGajG(B: (3U(B. 569-572s
Keywords: (3GdGSJKeGQs; (3GdGSges; (3GdGhQGb GdeGdjIs; (3GdHhQUGJs